Review on remote OBD system data analysis of heavy-duty diesel vehicle - LIU Haoye; ZHANG Xiaowen; REN Shuojin; WANG Tianyou* (能源环境保护)
Heavy-duty diesel vehicle is an important source of nitrogen oxides and particulates in the atmosphere. The remote OBD system combines OBD technology with wireless communication technology to send the vehicle operation data, emission status and fault information to the regulatory authorities, so as to realize the whole life-cycle emission monitoring of heavy-duty diesel vehicles. At present, the main research directions regarding the data analysis of the remote OBD system for heavy-duty diesel vehicles include high-emission vehicle identification and fault diagnosis, tampering detection of aftertreatment system and analysis of vehicle performance characteristics under real-world driving conditions. This paper summarizes the research progress in the above three directions. The key issue of high-emission vehicle identification is to identify whether the vehicle emissions comply with emission regulation requirements based on the NO_x concentration data and limited vehicle status data provided by the remote OBD system. The key issue of the tampering detection of aftertreatment system is how to balance the accuracy and complexity of the tampering detection algorithm. The analysis of vehicle performance characteristics under real-world driving conditions provides an important reference for the formulation of emission regulations and the upgrading of powertrain technology.